Incomplete contract in private finance initiative(PFI): a modified Delphi study - Mansor, Nur Syaimasyaza; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (American Scientific Publishers, 2017)
Incomplete contract (IC) is a contract that fails to state all the parties’ rights and obligations, has gaps and ambiguities in its terms and conditions. Literature had discussed the reasons of IC are due to long duration of the contract, high risk and uncertainty, high transaction cost, bounded rationality, and others. Private Finance Initiative (PFI) contracts are also inevitably incomplete. PFI involves the private sector to finance, design, construct, operate and maintain the asset through 20-30 years concession period. It is almost impossible for the parties to specify all potential contingencies that might occur throughout the contract period. IC could provide the necessary flexibility in the contract to deal with uncertainty. Nonetheless, it can cause inefficiencies and costs, hold-up problem, and others. This paper aims to investigate the presence of IC in PFI contract in Malaysia through a two-round modified Delphi method. 12 clauses are identified incomplete through literature review and content analysis, and it became the basis of the semi-structured questionnaire for the modified Delphi approach. The statistical descriptive analysis was used to analyze the data and the results found that out of 12 clauses, only 10 clauses were considered incomplete.